Near-infrared fluorescence probe with a large Stokes shift for selectively imaging of hydrogen peroxide in living cells and in vivo. (January 2022) - Gao, Meng-Jiao; Hua, Yun; Xu, Jia-Qi; Zhang, Li-Xia; Wang, Shuo; Kang, Yan-Fei
Abstract: In this work, we have designed and synthesized a large stokes shift and near-infrared (NIR) probe DCM-HNU for visualization of H2 O2 in both living HeLa cells and zebra fish. The probe DCM-HNU was structured based on phenylborate pincinol ester as the recognition group connecting DCM-OH via nucleophilic substitution reaction. The probe possessed large stokes shift (205 nm), near-infrared (NIR) emission (658 nm). 0.17 μM detection Limit, 10, 550 L·mol −1 cm −1 molar extinction coefficient, 2.06 × 10 −3 S −1 reaction rate constant, and excellent selectivity proved the condition for practical application. There was a good linear relationship between fluorescence intensity and H2 O2 concentration from 0 to 200 μM (R 2 = 0.9955) to facilitate quantitative analysis of H2 O2 . More importantly, the probe is able to visualize exogenous and endogenous H2 O2 in living HeLa cells and zebra fish. The superior properties of the probe provide potential for exploring the function and participation of H2 O2 in biological systems. Highlights: Large stokes shift (205 nm), near-infrared (NIR) emission (658 nm). The probe is able to visualize exogenous and endogenous H2 O2 .